The impact of palliative care on cancer patients’ quality of life: systematic review and meta-analysis - Kassianos, Angelos P.; Ioannou, Myria; Koutsantoni, Marianna (My University, 2015)
Background: The aim of the study is to investigate and assess the quality of evidence on the impact of palliative care in cancer patients' health-related quality of life (HRQOL). Methods: A systematic review will be undertaken. The following databases will be searched using specific keywords for published papers: PsycInfo, PubMed, Embase, Medline and Cinahl. All of the papers retrieved will be qualitatively assessed on a number of quality criteria. Consistency among the observational ratings will be assessed using the inter-rater reliability. Studies that achieve certain quality criteria will be included in a meta-analysis which will be run based on the principles of the random-effects models. Expected results: It is expected that evidence will designate that palliative care has an impact on cancer patients' HRQOL. Current stage of work: Currently the preliminary searches were conducted and the abstracts of identified studies are assessed against the inclusion criteria. Discussion: This study can guide policy and practice on palliative care integration. The study can also benefit the understanding of the association between psychosocial factors enhanced by palliative care and an individual's HRQOL.